EXPERIMENTAL DETERMINATION OF OHMIC RESISTIVITY OF FLY ASH FOR DESIGN OF ELECTROSTATIC PRECIPITATORS - Ozawa, M.; Yanagihara, J. I. (Revista de Engenharia Térmica, 2005)
The objective of the present work is to determine the ohmic resistivity of fly ashes collected at electrostatic precipitators (ESPs) attached to boilers burning Brazilian coals. An experimental device to measure the fly ash resistivity was designed and constructed; tests were conducted according to accepted standards in other countries. It was the first time that this kind of measurement was conducted for Brazilian coals. The tested materials were collected from ESPs operating in the southern region of Brazil, where the mineral coal is commonly used. The ohmic resistivity of the tested materials was smaller compared to mineral coals from abroad. The resistivity of the fly ash increased when the temperature was raised, which is in accordance with reported results for mineral coals from abroad. Tests with particulate material collected from the electrostatic precipitator (ESP) of a biomass boiler showed that its ohmic resistivity is much lower than the resistivity of fly ash from the mineral coal. This means that the ESP for biomass boiler should be smaller, which is in accordance with the industrial practice. Based on the experimental results, practical comments about ESP sizing were made in order to assist engineers and technicians dealing with the problem of gas treatment in coal combustion.